Time-series momentum: Is it there? - HUANG, Dashan (Institutional Knowledge at Singapore Management University, 2020)
Time-series momentum (TSM) refers to the predictability of the past 12-month return on the next one-month return, and is the focus of several recent influential studies. This paper shows, however, that asset-by-asset time-series regressions reveal little evidence of TSM, both in- and out-of-sample. While the t-statistic in a pooled regression appears large, it is not statistically reliable as it is less than the critical values of parametric and non-parametric bootstraps. From an investment perspective, the TSM strategy is profitable, but its performance is virtually the same as that of a similar strategy that is based on historical sample mean and does not require predictability. Overall, the evidence on TSM is weak, particularly for the large cross section of assets.